Development of selectable markers for mitochondrial transformation in yeast - Ho, Mei San; Toh, Wai Keat; Chang, Shu Ting; Yap, Kiao Huio; Loh, Pek Chin; Namasivayam, Parameswari; Wong, Hann Ling (University of Malaya, 2024)
Mitochondria, present in most eukaryotic organisms, are crucial for energy production and essential for cellular functions. Sequencing of the complete mitochondrial genome of Saccharomyces cerevisiae in 1998 has paved the way for mtDNA gene editing, enabling the study of mitochondrial function and potential gene therapies for mitochondrial diseases. Effective selectable markers are crucial for addressing heteroplasmic mtDNA issues after mitochondrial transformation. Antibiotic resistance (AbR) marker genes aadA1, cat, and hph confer resistance to streptomycin, chloramphenicol, and hygromycin B, respectively. This study aimed to explore the feasibility of employing these AbR markers for selecting transformed yeast cells. Additionally, the usefulness of these AbR genes as selectable markers for yeast mitochondrial transformation was assessed by fusing a mitochondrial targeting signal (MTS) to the N-terminus of these genes using overlapping PCR. The minimal inhibitory concentration (MIC) of yeast transformants expressing various AbR genes, with or without MTS fusion, was determined using the agar dilution method. Yeast transformants expressing aadA1, cat, and hph, with or without MTS fusion, displayed resistance to streptomycin (>10 mg/mL), chloramphenicol (up to 6 mg/mL), and hygromycin B (up to 4 mg/mL), respectively. MICs were similar between AbR and MTS-tagged AbR yeast transformants. To assess mitochondrial targeting, GFP was fused to the C-terminus of cat and MTS-cat gene constructs. Fluorescence microscopy confirmed MTS-tagged CAT-GFP localization to yeast mitochondria, while CAT-GFP showed cytoplasmic localization. The fluorescence microscopy results were confirmed by Western blotting. This study demonstrated that yeast transformants expressing aadA1 exhibit a significant level of streptomycin resistance (>10 mg/mL), suggesting that aadA1-mediated streptomycin resistance has the potential to serve as a selectable marker for mitochondrial transformation in yeast.